Penggunaan Media Audiovisual dalam Pengajaran Musik - Wiflihani Wiflihani (Universitas Negeri Medan, 2021)
This article aims to explain the use of audiovisual media in learning music. To carry out teaching through audiovisual media, it is necessary to prepare a learning unit, choose the correct audiovisual media and adjust it to a musical instrument or teaching topic, to know the duration of the audiovisual media, which must be adjusted to the lesson hours. To prepare students, they are given a general explanation of the contents of the learning video, then they play back and prepare the equipment for a smooth learning experience. Follow-up: After watching a film or video, the teacher also did examples of playing music, thinking, and asking questions to students to find out how well the students understood the material.